ABOUT CHEMICAL COMPOSITION OF SUPERGIANT PMMR145 IN SMALL MAGELLANIC CLOUD. OSMIUM. - Gopka, V. F.; Shavrina, A. V.; Vasilyeva, S. V.; Andrievsky, S. M. (Одеські астрономічні публікації, 2012)
The abundance analysis of six Ksupergiants of the Small Magellanic Cloud (Hill 1997) showed that the heavier elements (La, Ce, Nd, Eu) have the excess relative to iron [El/Fe]=+0.4 dex, on average, for the sample of five stars (PMMR23, PMMR27, PMMR48, PMMR102, PMMR145). We made the identification of spectral lines in the spectrum of PMMR145 based on the comparison of synthetic and observed spectra. The absorption lines of elements heavier than lanthanides including osmium were identified and abundance of osmium was found ([Os/Fe]=0.59 dex).